Perceptions of primary healthcare providers for screening and management of mental health disorders in India: a qualitative study - Sangwan, Ramesh Kumar; Kansara, Darshana; Matoria, Santosh; Ali, Haider; Khetan, Mukti; Singh, Vishal; Thakor, Mahendra; Huda, Ramesh Kumar; Babu, Bontha V. (Frontiers in Public Health, 2024)
Introduction Individuals experiencing mental health disorders encounter numerous challenges while accessing mental healthcare services. Despite the inclusion of mental health in the primary healthcare system, screening and managing mental health disorders remain significantly overlooked. Therefore, there is a need to understand the perceptions of healthcare providers in primary care settings, identify the challenges faced, and gather suggestions for effective mental healthcare delivery. Methods The present qualitative study was conducted in 13 primary healthcare facilities in the Jodhpur district of Rajasthan, India, from 2023 to 2024 among 25 primary healthcare providers. Semi-structured interview guides were developed for each category of primary healthcare provider, including Medical Officers, Community Health Officers, and General Nurse Midwives, Auxiliary Nurse Midwives and in-depth interviews were recorded, transcribed, and thematically analyzed using codes and sub-codes. Results Results are summarized under the themes: (i) Navigating Mental Healthcare in Primary Healthcare Facilities, (ii) Challenges and Barriers in Mental Healthcare Delivery, (iii) Recommendation for Enhancing Mental Healthcare Services, and (iv) Approaches for Comprehensive Capacity Building Training and Module and further findings of each theme are presented under various sub-themes. Conclusion The findings suggest that despite a perceived competence in providing mental health services, there were substantial levels of negative attitudes towards mental health disorders among participants and provide insights for policymakers and healthcare professionals to develop targeted interventions and improve mental healthcare delivery at primary care facilities.